Detection of potentially inappropriate prescribing in older patients with the GheOP³S-tool: completeness and clinical relevance. Issue 2 (4th March 2019) - Kympers, C.; Tommelein, E.; Van Leeuwen, Ellen; Boussery, K.; Petrovic, M.; Somers, A.
ABSTRACT: Objectives: The Ghent Older People's Prescriptions community Pharmacy Screening (GheOP 3 S-) tool was recently developed as an explicit screening method to detect Potentially Inappropriate Prescribing (PIP) in the community pharmacy. We aimed to validate the GheOP 3 S-tool as an effective screening method for PIP.Methods : All patients admitted to the acute geriatric ward of the Sint-Vincentius hospital (Belgium) were consecutively screened for inclusion (≥70 years, ≥5 drugs chronically). PIP prevalence was evaluated by applying the GheOP 3 S-tool on the complete medication history. For each PIP-item, clinical relevance of the detected item, relevance of proposed alternative and subsequent acceptance by the treating geriatrician and a general practitioner were evaluated. Additionally, contribution to the current admission and preventability was assessed by the geriatrician. The completeness of a PIP-screening with the GheOP 3 S-tool was evaluated through comparison with the adapted Medication Appropriateness Index (aMAI).Results : We detected 250 GheOP 3 S-items in 57 of 60 included patients (95%) (median: four PIP-items per patient; IQR: 3–5). Both the geriatrician and the general practitioners scored the clinical relevance of the detected items 'serious' or 'significant' in over 70% of cases. Proposed alternative treatment plans were accepted for 79% of the PIP-items ( n = 198). The aMAI detected 536 items, of which 145 were also detected by the GheOP 3 S-tool. A total of 119 PIP-items were additionally detected by the GheOP 3 S-tool.Conclusion : The clinical relevance of the PIP-items detected with the GheOP 3 S-tool is high, likewise the acceptance rate of proposed alternatives.